Parental care and reproductive behavior of the minute dappled glassfrog (Centrolenidae: Centrolene peristictum) - Salgado, Ana (2018)
We studied the reproductive biology of the endangered glassfrog Centrolene peristictum in a cloud forest of the Northwest slopes of the Ecuadorian Andes (15 December 2009-16 April 2010). During this season, 78 males were detected, most of which were calling from the underside of leaves of riverine vegetation at night. Their call was recorded and analyzed, and it resembles a cricket chirp. Each call has one pulsed note with a duration of 0.036-0.087 s and a dominant frequency of 6,470.7-7,278.2 Hz. Females placed the egg clutches mostly on the underside of leaves (92%), and eggs are guarded by males. Through a male removal experiment, we show that clutches without parental care have a significantly lower hatching rate than control clutches, and prolonged developmental time. Clutch mortality was mainly because of desiccation, with 64% of death in the removal group and 18% in control (P = 0.001, n = 60); other important causes of mortality of the egg clutches involved predation and parasitism. © 2018 Brazilian Society of Herpetology.